Etika Profesi Pegawai Swasta di Bidang Marketing : Analisis Yuridis dan Implementasi dalam Praktik Bisnis Moderngawai Swasta Di Bidang Marketing: Analisis Yuridis Dan Implementasi Dalam Praktik Bisnis Modern - Lutfiana Lukman; Roy Marthen Moonti; Ibrahim Ahmad; Muslim A. Kasim (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines the ethical aspects of private sector employees' profession, particularly in marketing, within the context of Indonesian business law. The main focus of the research is to analyze the legal framework governing marketing professional ethics, its implementation in modern business practices, and the challenges and solutions faced in its enforcement. The methodology used is normative juridical with a statutory and case analysis approach. The research findings indicate that the regulation of marketing professional ethics still requires strengthening, especially in the digital era. This research examines the ethical aspects of private sector employees' profession, particularly in marketing, within the context of Indonesian business law. The main focus of the research is to analyze the legal framework governing marketing professional ethics, its implementation in modern business practices, and the challenges and solutions faced in its enforcement. The methodology used is normative juridical with a statutory and case analysis approach. The research findings indicate that the regulation of marketing professional ethics still requires strengthening, especially in the digital era.